ANALYSIS OF THE EFFECT OF LOCAL TAX AND POPULATION ON LOCAL ORIGINAL REVENUE IN BIREUEN DISTRICT IN 2007-2016 - Risma Yanti; Khairil Anwar (Journal of Malikussaleh Public Economics, 2018)
This study aims to Determine the Effect of Local Taxes and the Number of Population on Local Original Revenue in Bireuenn District in 2007-2016. The Data used in this study are secondary Data sourced from Bireuen District Central Bureau of Statistics (BPS) 2007-2016. The method of data analysis used in this study is the Multiple Linear Regression models. The results Showed that the local tax partially has a significant and negative effect on the Local Original Revenue in Bireuen District and the Population has a positive and significant effect on the Local Original Revenue in Bireuen District. Whereas simultaneously the variables of Local Taxes and Population have a positive and significant effect on Original Local Revenue in Bireuen District in 2007-2016.